2013
DOI: 10.1007/s10508-013-0190-1
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Possible Functions of Kissing in Romantic Relationships

Abstract: Recent research suggests that romantic kissing may be utilized in human sexual relationships to evaluate aspects of a potential mate's suitability, to mediate feelings of attachment between pairbonded individuals, or to facilitate arousal and initiate sexual relations. This study explored these potential functions of romantic kissing by examining attitudes towards the importance of kissing in the context of various human mating situations. The study involved an international online questionnaire, which was com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 56 publications
3
36
0
Order By: Relevance
“…It has also previously been found that romantic kissing is used in assessing a mating partner's desirability (Hughes et al 2007;Wlodarski and Dunbar 2013). The results of the current study synthesize these findings by showing that attitudes towards romantic kissing vary across the menstrual cycle and are significantly associated with the fluctuation of menstrual hormones.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…It has also previously been found that romantic kissing is used in assessing a mating partner's desirability (Hughes et al 2007;Wlodarski and Dunbar 2013). The results of the current study synthesize these findings by showing that attitudes towards romantic kissing vary across the menstrual cycle and are significantly associated with the fluctuation of menstrual hormones.…”
Section: Discussionsupporting
confidence: 82%
“…Previous research has found that the cross-culturally prevalent custom of romantic kissing is one mate cue that can been exploited in the assessment of potential mating partners (Hughes et al 2007;Wlodarski and Dunbar 2013). This research also suggests that females are more reliant on kissing as a mate assessment device and are unwilling to have sexual intercourse with a partner without first kissing them; rate "bad kissers" as less attractive overall; and tend to base evaluations of kissing ability on chemical cues (such as breath and taste of mouth).…”
mentioning
confidence: 99%
“…Prior research has found that kissing serves the purposes of relationship maintenance and assessment of potential romantic partners for sexual compatibility (Hughes et al, 2007; Wlodarski & Dunbar, 2013). Because of kissing’s distinct significance, sexual behaviors may have different meanings when kissing is present versus absent.…”
Section: Discussionmentioning
confidence: 99%
“…In order to understand the role of sexual behavior patterns in emotional health, it is necessary to assess additional sexual behaviors. Although oral and penetrative sex are important to study, kissing and touching are also key to understanding relational outcomes because of their associations with affection and relationship maintenance (Hughes, Harrison, & Gallup, 2007; Wlodarski & Dunbar, 2013). One person-oriented study of adolescent girls found variation in the likelihood of kissing and touching in different latent classes (Hipwell et al, 2011), but it is unknown how these behaviors factor into sexual repertoires for boys or beyond mid-adolescence.…”
Section: The Value Of a Person-oriented Approachmentioning
confidence: 99%
“…Kirshenbaum (2011) claimed that kissing is a near universal; however, this conclusion was based on a very broad definition of kissing, which included various non-romantic contexts and greatly differing levels of physical context. Kissing seems to have several potential beneficial functions, including assessing the genetic fitness (Thornhill & Gangestad, 1999) and compatibility (Wedekind, Seebeck, Bettens, and Paepke, 1995) of partners, strengthening preexisting relationships (Wlodarski & Dunbar, 2013), and exchanging commensal microbiota (MontielCastro, González-Cervantes, Bravo-Ruiseco, & Pacheco-López, 2013). Despite the purported benefits of kissing, all of its forms do not appear to be universal.…”
Section: Romantic Sexual Kissingmentioning
confidence: 99%